From mass to my - Chapman, Tony (Henry Stewart Talks, 2009)
Attention, the oxygen of communication, Shouting with media, The media becomes a dominant part in life, Market saturation, Why buying value is now viewed as buying smart, The consumers are in control of media, The paradox of choice, Consumers want personalization and experiences, Trading up to iconic brands, Trading down to brands or retailers on sale, Decisions are made in your stores, Generation facebook, Know your consumer, The power of insights, The intersection points, To think, act and market like a fashion brand, The process begins by creating a story